Objectification and Violence Against Women: The Spanish Validation of the Interpersonal Sexual Objectification Scale-Perpetration Version - Sánchez-Fuentes, María del Mar (Violence against women, 2025)
The aim of this study was to validate the Interpersonal Sexual Objectification Scale-Perpetration Version (ISOS-P), a measure that assesses sexual objectification perpetration. The sample consisted of 356 heterosexual men of Spanish nationality. Confirmatory factor analysis was performed. The Spanish validation of the ISOS-P comprises 15 items and showed a trifactorial structure. McDonald’s omega values ranged from 0.71 to 0.80, and evidences of validity are shown by positive correlations with the endorsement of a positive attitude toward rape and having perpetrated several sexual aggression types. The Spanish validation of the ISOS-P is a valid and reliable scale.